2001
DOI: 10.1002/path.1028
|View full text |Cite
|
Sign up to set email alerts
|

Fas receptor‐mediated apoptosis: a clinical application?

Abstract: Fas is a membrane protein belonging to the death receptor family. Cross-linking of Fas by its ligand, FasL, or agonistic anti-Fas antibodies, induces apoptosis of cells expressing Fas on the membrane by triggering a cascade of caspases. Since many different tumours express Fas on their membrane, targeting Fas-mediated apoptosis by anti-Fas antibodies may be a promising anticancer therapy. Unfortunately, not all Fas-expressing cells are sensitive to Fas-mediated apoptosis. This has resulted in the discovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 127 publications
3
91
0
1
Order By: Relevance
“…The upregulation of CD95 can sensitise tumour cells to the CD95 death signal (Timmer et al, 2002). In the present study, we have found that cisplatin treatment increased the CD95 membrane expression.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The upregulation of CD95 can sensitise tumour cells to the CD95 death signal (Timmer et al, 2002). In the present study, we have found that cisplatin treatment increased the CD95 membrane expression.…”
Section: Discussionsupporting
confidence: 63%
“…However, almost no studies have looked into whether anticancer drugs can change TRAIL-receptor membrane expression, while this effect has been described for CD95 (Timmer et al, 2002). Furthermore, it is not known whether this change in receptor expression levels at the cell surface or expression levels of pro-and antiapoptotic proteins are the key determinants for sensitivity to TRAIL or CD95L.…”
mentioning
confidence: 99%
“…The Fas gene has been shown to be mutated in both hematopoietic malignancies (0-65%) and solid tumors (0-28%). 17 Among the hematopoietic malignancies, high frequencies of Fas mutations occur in thyroid lymphoma (65.4%), cutaneous T-cell lymphoma (59%), and nasal NK/T cell lymphoma (50%). Among solid tumors, Fas mutations occur frequently in bladder transitional cell carcinoma (28%) and burn scar-related squamous cell carcinoma (14.3%).…”
Section: Death Receptors and Cancermentioning
confidence: 99%
“…Among solid tumors, Fas mutations occur frequently in bladder transitional cell carcinoma (28%) and burn scar-related squamous cell carcinoma (14.3%). 17 Compared to Fas, the frequencies of DR4 and DR5 mutations detected in cancers including lung, head and neck, breast, bladder, gastric and hepatocellular carcinomas, non-Hodgkin's lymphoma and chronic myelogenous leukemia are very low (0-10.6%). [18][19][20] Downregulation of expression of death receptors has also been observed in cancer.…”
Section: Death Receptors and Cancermentioning
confidence: 99%
“…At the molecular level, binding of FasL to Fas induces receptor trimerisation, followed by the binding of Fas-associated death domain (FADD) with caspase 8 and/or 10 to the intracellular death domain of Fas. Caspase activation within this complex initiates cleavage and activation of an intracellular cascade of effector caspases (e.g., caspases 3, 6, and 7), eventuating in cleavage of specific death substrates and apoptosis (Timmer et al, 2002). Thus, in tumours expressing Fas, targeting of Fas-mediated apoptosis could be a promising therapy.…”
mentioning
confidence: 99%